Sikap Sopan Santun Mahasiswa Prodi Manajemen Informasi Kesehatan di Asrama Stikes Santa Elisabeth Medan - Ronatal Miasari Manurung; Sitompul, Agnes Louise Lasmaida; Daniel Fanando Dachi (Yayasan Literasi Sains Indonesia, 2024)
Nowdays, politeness is no longer a barrier to socializing with various groups. Freedom of opinion, the environment, developments over time and technology are the reasons that make manners shift. Manners are an important element in socializing, because by showing good manners a person can be respected and like by their existence as a social being. In this case, good manners can provide many benefits or influences, both good and bad, on oneself and others. The aim of this research is to determine the level of politeness of santa elisabeth medan health information management study program students in the dormitory environment. The research used random sampling and cross sectional design, and data colection was carried out trough direct observation. The population used in the research were MIK students with a sample size of 27 respondents and 15 questions indicators. Data colection techniques used questionnaires as primary data, and journals and books as secondary data. The results of the research show that behavior of 25 MIK students was classfied as good, namely (60%), and 2 were classified as poor namely (20%). This can be seen from students habits in everyday life regarding their lack of politeness